Gas Pressure Measurement On Rocket Chamber Based On Strain Gauge Sensor - Anggara Trisna Nugraha; Rahman Arifuddin (JEEMECS (Journal of Electrical Engineering, Mechatronic and Computer Science), 2020)
The use of rocket technology is currently also widely used for research. The rocket itself is a flying vehicle that moves by getting a boost through the combustion reaction that occurs in the rocket. The rocket itself can launch the load to the desired destination. In the field of science and technology, continuous efforts are required to realize the development of this rocket in order to achieve independence and prosperity. In the field of science and technology, continuous efforts are required to realize the development of this rocket in order to achieve independence and prosperity. The implementation of the strain gauge sensor through the MPXV7002DP gas pressure sensor obtained the amount of gas pressure during the combustion of the propellant in the rocket chamber, where the gas pressure can be measured, processed through the Arduino Uno microcontroller. The system can measure the maximum pressure up to 380 kPa and then the system can check any changes in voltage level to prove if there is a leak in the rocket.